“Estilo de apego y violencia doméstica en mujeres atendidas en la unidad judicial especializada en violencia contra la mujer y la familia del consejo de la judicatura de Riobamba, periodo mayo – octubre 2016” - Hurtado Herrera, Erika Tatiana (2017)
"Style of Attachment and Domestic Violence in Women that catered in the Judicial Unit specialized in Violence against Women and the family of the Council of the Judiciary of Riobamba, from May until October 2016". ABSTRACT: The present investigation was carried out in the Judicial Unit specialized in Violence against Women and the family of the Council of the Judiciary of Riobamba, from May until October 2016. Its general objective is to determine the Style of Attachment and its influence on Domestic Violence in Women who attended the mentioned institution. The design used was mixed since it combines quantitative - qualitative and non - experimental techniques; the type of research is field, documentary and transversal; the level of the research was descriptive and correlational. For the sample, populations of 30 women between 30 and 60 years of age, taking into account the inclusion and exclusion criteria, considering the validity of the Scale. The instrument used for the data collection was: Adult Attachment Scale of María Martina Casullo and Mercedes Fernández Liporace. The statistical analysis used for these qualitative variables was a description of frequencies and percentages to determine the relationship between the Attachment Style and the existing Domestic Violence, through the Pearson Chi - Square statistical program in order to determine the level of significance between the relation of These variables The most relevant results obtained from the application of the psychological reagent used are: 23 women corresponding to 77% of the population present anxious attachment style of which 14 women belonging to 61% of the population present Psychological Violence. The use of statistical analysis was determined the level of significance showed a value of P < 0.05 (0.046) which indicated that the relationship between these two variables was statistically significant, thus confirming the hypothesis that the attachment style influences In domestic violence. Once the hypothesis was verified, a psychotherapeutic intervention plan was developed for women victims of Domestic Violence who attend the Specialized Judicial Unit on Violence against Women and the Family of the Judicial Council of Riobamba.